2018
DOI: 10.3390/ijms19113399
|View full text |Cite
|
Sign up to set email alerts
|

Reconstituted HDL (Milano) Treatment Efficaciously Reverses Heart Failure with Preserved Ejection Fraction in Mice

Abstract: Heart failure with preserved ejection fraction (HFpEF) represents a major unmet therapeutic need. This study investigated whether feeding coconut oil (CC diet) for 26 weeks in female C57BL/6N mice induces HFpEF and evaluated the effect of reconstituted high-density lipoprotein (HDL)Milano (MDCO-216) administration on established HFpEF. Eight intraperitoneal injections of MDCO-216 (100 mg/kg protein concentration) or of an equivalent volume of control buffer were executed with a 48-h interval starting at 26 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…MDCO-216 has been tested in healthy volunteers and patients with stable CAD, showing modulation of lipid parameters and an increase of cholesterol efflux with no adverse effects [129,130]. More recently, MDCO-216 has also reported, at an experimental level, to revert heart failure progression in Type 2 diabetic mice as well as restore cardiac function [154], lower myocardial acetyl-coenzyme A carboxylase levels, and decrease myocardial transforming growth factor-β1 [155]. CSL112, a reconstituted, infusible, plasma-derived ApoA-I structure, is another promising HDL-mimetic.…”
Section: Potential Clinical Applicability Of Hdl Mimeticsmentioning
confidence: 99%
“…MDCO-216 has been tested in healthy volunteers and patients with stable CAD, showing modulation of lipid parameters and an increase of cholesterol efflux with no adverse effects [129,130]. More recently, MDCO-216 has also reported, at an experimental level, to revert heart failure progression in Type 2 diabetic mice as well as restore cardiac function [154], lower myocardial acetyl-coenzyme A carboxylase levels, and decrease myocardial transforming growth factor-β1 [155]. CSL112, a reconstituted, infusible, plasma-derived ApoA-I structure, is another promising HDL-mimetic.…”
Section: Potential Clinical Applicability Of Hdl Mimeticsmentioning
confidence: 99%
“…HDL also has anti-fibrotic effects. HDL decreases transforming growth factor-ß1-induced collagen accumulation 53 and reduces transforming growth factor-ß1 in the myocardium 24 . Furthermore, HDL has been demonstrated to decrease endothelial-mesenchymal transition in aortic endothelial cells in vitro induced by transforming growth factor-ß1 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Apo A-i Milano nanoparticles. MDCO-216 is a 1:1 by weight complex of dimeric apo A-I Milano produced by recombinant DNA technology and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine 24 and was supplied by The Medicines Company (Parsipanny, NJ, USA) as a solution in buffer containing mannitol 43.6 mM, sucrose 181 mM, NaH 2 PO 4 •2H 2 O 3.46 mM, and 8.43 mM Na 2 HPO 4 •7H 2 O. Non-denaturing polyacrylamide gradient-gel electrophoresis has previously demonstrated that these nanoparticles are characterised by an apparent diameter of 8 nm and that no free apoA-I Milano was observed 61 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations